Role of adiponectin and leptin on body development in infants during the first year of life - Gasparoni Antonella; Stronati Mauro; Pagani Sara; Travaglino Paola; Arvigo Marica; Meazza Cristina; Bozzola Elena; Bianco Carolina; Bozzola Mauro (BMC, 2010)
Abstract Background The control of growth and nutritional status in the foetus and neonate is a complex mechanism, in which also hormones produced by adipose tissue, such as adiponectin and leptin are involved. The aim of this study was to evaluate levels of adiponectin, leptin and insulin in appropriate (AGA) and small for gestational age (SGA) children during the 1st year of life and to correlate these with auxological parameters. Methods In 33 AGA and 29 SGA infants, weight, length, head circumference, glucose, insulin, adiponectin and leptin levels were evaluated at the second day of life, and at one, six and twelve months, during which a portion of SGA could show catch-up growth (rapid growth in infants born small for their gestational age). Results Both total and isoform adiponectin levels were comparable between AGA and SGA infants at birth and until age one year. These levels significantly increased from birth to the first month of life and then decreased to lower values at 1 year of age in all subjects. Circulating leptin concentrations were higher in AGA (2.1 ± 4.1 ng/ml) than in SGA neonates (0.88 ± 1.03 ng/ml, p < 0.05) at birth, then similar at the 1st and the 6th month of age, but they increased in SGA from six months to one year, when they showed catch-up growth. Circulating insulin levels were not statistically different in AGA and SGA neonates at any study time point. Insulin levels in both AGA and SGA infants increased over the study period, and were significantly lower at birth compared to one, six and 12 months of age. Conclusions During the first year of life, in both AGA and SGA infants a progressive decrease in adiponectin levels was observed, while a difference in leptin values was correlated with the nutritional status.